Motivation and learning: Implications for fundamental nursing education (Research, Society and Development, 2025)
Motivation is revealed as an essential element in nursing education, since students must integrate theoretical knowledge, technical skills, and ethical-human principles in their educational and care practices. The study is based on a critical analysis of the literature on motivation and learning in nursing education. The objective is to understand, in a reflective way, the role of motivation—both intrinsic and extrinsic—in the learning process of nursing, analyzing its implications for academic performance, ethical formation, and the development of pedagogical strategies that foster engagement, autonomy, and humanized care. The bibliographic review included scientific articles, reviews, dissertations, theses, and books published in Portuguese, English, and Spanish, excluding duplicate or unrelated materials. The data were organized into three thematic categories: theoretical foundations of motivation; implications of motivation for learning; and pedagogical strategies for its strengthening. The reflective analysis integrated classical and contemporary references, allowing for a broader understanding of the motivational phenomenon in the context of nursing education. As the study is based exclusively on secondary sources, submission to an ethics committee was not required; however, current ethical and academic principles were respected. The results show that identifying and stimulating motivation in educational environments that promote autonomy, engagement, and institutional support contribute significantly to the formation of competent, critical nurses committed to comprehensive human care.